2012
DOI: 10.1111/j.1432-2277.2012.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET/CT predicts early tumor recurrence in living donor liver transplantation for hepatocellular carcinoma

Abstract: Summary The prognosis including 18F‐fluorodeoxyglucose positron emission tomography/computed tomography (18F‐FDG‐PET/CT) for the early recurrence for hepatocellular carcinoma (HCC) after living donor liver transplantation (LDLT) was not well established. Consecutive patients who underwent 18F‐FDG‐PET/CT and subsequent LDLT for HCC from March 2005 to June 2011 were enrolled. The 191 patients with a median follow‐up of 26.1 months were evaluated. There were 20 patients (10.5%) with early recurrence (≤6 months), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 31 publications
0
59
0
Order By: Relevance
“…In some previous studies, the metabolic status of HCC as seen on 18 F-FDG PET was the only significant factor predicting long-term survival (21) and early recurrence (,6 mo) after liver transplantation (22). Other studies found some additional factors to be significant, such as the metabolic status of the HCC, the extent of vascular invasion (23,24), and the degree of differentiation (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies, the metabolic status of HCC as seen on 18 F-FDG PET was the only significant factor predicting long-term survival (21) and early recurrence (,6 mo) after liver transplantation (22). Other studies found some additional factors to be significant, such as the metabolic status of the HCC, the extent of vascular invasion (23,24), and the degree of differentiation (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor number and size was very limited to predict important pathologic variables including microvascular invasion and differentiation. Recently, biomarkers, response to transarterial chemoembolization (TACE), gene-expression profile, PET/CT, AFP, and PIVKA-II, have been used for the assessment of tumor aggressiveness (5,(10)(11)(12)(34)(35)(36)(37)(38)(39).…”
Section: Predicting Pathologic Resultsmentioning
confidence: 99%
“…In LDLT setting, although the patients had the advanced HCC beyond the Milan criteria, the operation could be performed as the willingness of donor and informed consent. Therefore, many criteria using various indicators α-fetoprotein (AFP), protein induced by vitamin K absence or antagonist-II (PIVKA-II), 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and tumor morphology have been proposed (5,(8)(9)(10)(11)(12)(13)(14). In HCC patients, tumor characteristics, including differentiation grade and microvascular invasion, are well-known independent prognostic factors for overall survival (OS) and disease-free survival (DFS) following LT (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FDG PET/CT is widely used to assess for extrahepatic metastases prior to liver transplantation (6). PET/CT has also been found to be useful as a predictive parameter for evaluation of early HCC recurrence after liver transplantation (7). In light of the increasing use of PET/CT in liver transplant patients, it is important to be aware of lesions that mimick malignancy.…”
Section: Figurementioning
confidence: 99%